Dampak Pengesahan Undang-Undang Cipta Kerja terhadap Investasi Dan Ketenagakerjaan di Indonesia - Muhammad Rifqi Wanasella (International Forum of Researchers and Lecturers, 2026)
This study examines the implications of the enactment of Law Number 6 of 2023 on Job Creation regarding labor rights protection, particularly in the areas of wages and leave entitlements. The results show that the Job Creation Law does not entirely revoke or modify the provisions previously established under Labor Law Number 13 of 2003, as unaddressed articles in the Job Creation Law remain legally binding. Concerning wages, the Provincial Minimum Wage serves as the primary benchmark, while the determination of Regency/City Minimum Wage has become discretionary, which may place workers at a disadvantage in areas with elevated living costs. Regarding leave entitlements, certain rights specific to female workers, including menstrual leave, maternity leave, and breastfeeding rights, were not re-regulated under the Job Creation Law, meaning they continue to apply under the previous regulation. Despite this, actual implementation in the field reveals widespread non-compliance by employers. For this reason, sustained government supervision is indispensable to guarantee that labor rights protection remains upheld following this legislative reform.